PEMBELAJARAN MUFRADAT DENGAN PERMAINAN LOMPAT KOTAK - Mujiburrohman, Mujiburrohman; Nurjannah, Nurjannah; Syafi'i, Ahmad Helwani (Universitas Muhammadiyah Mataram, 2023)
To improve the ability of mufradat of Madrasah Ibtidaiyah students, a fun learning process is needed. This study aims to find out innovations in learning Arabic mufradat with game media. The method used in this research is literature review, which is an assessment of the concepts and theories used based on the available literature. The results of the discussion in this study mufradat learning at Madrasah Ibtidaiyah can be done with a box jump game. Where students will learn outside the classroom to play, jump, memorize, recite and associate mufradat. So that mufradat learning is carried out in a fun way and makes learning more effective.